Analisis Pembelajaran Problem Solving dengan Media Kartu dalam Pembelajaran Pendidikan Pancasila pada Siswa Kelas 2 - Errina Romadhona Shal Sabila; Octarina Hidayatus S.; Endang Suprihatin (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2025)
This research aims to describe Problem Solving learning using card media in Pancasila Education learning material Types of House Rules for Grade 2 Elementary School students. This research uses a descriptive-qualitative research approach. This research was conducted on grade 2 students at SDN Bantengan 01, Wungu District, Madiun Regency. Data collection was carried out by direct observation, interviews and documentation. In analyzing the data, researchers used qualitative data analysis which was carried out interactively and took place continuously through data reduction, data display, and conclusion drawing or verification. The results of the research show that: (1) The application of Problem Solving learning using card media in Pancasila Education learning is carried out by applying certain learning steps, namely problem formulation, problem study, hypothesis formulation, data collection as material to prove the hypothesis, hypothesis verification, and determining solution options. (2) The learning outcomes achieved can be seen from the cognitive and affective aspects. Judging from the cognitive aspect, students show good abilities in understanding the lesson material (85% complete, 15% incomplete). Viewed from the affective aspect, students show activeness during the implementation of Problem Solving learning using card media in Civics learning (75%), including being able to understand problems (60%), being able to solve problems (40%), and being able to complete assignments (85%).